HALAL HARAM AKAD MURABAHAH BIL WAKALAH PEMBIAYAAN PERBANKAN SYARIAH - Nurhadi Nurhadi (Institut agama islam negeri Padangsidimpuan, 2020)
According to the Sharia Banking Act Number 1 of 2008 Article 1 paragraph 13, a contract is a written agreement between a Sharia Bank and a Sharia Business Unit with another party which contains the obligation for parties according to sharia principles. A contract is a legal relationship between parties that creates rights and obligations that are exchanged by the parties. An agreement is an event someone promises to another person or somewhere two people promise to do something or plan. All three are equated in linguistic and legal judicial review, together giving rise to rights and obligations between parties who share, together the concept of engagement in business law. The difference between the agreement and the contract according to the science of jurisprudence, the agreement is different from the agreement according to business law, but the difference is only in the term of use. By law and sharia, the murabahah and wakalah contracts are legalized. But if the murabahah bil wakalah agreement is not clear between the two contracts which one is used, there is obscurity (gharar), the law is haraam. But if the two contracts can be clear (not gharar) and separate (which one is the right one), then a transaction with two contracts is permitted, for example murabahah bil wakalah transaction, by means of the wakalah contract, then the murabahah contract, then this contract is enforced.